Appointment reminders by text message in a safety net health care system: a pragmatic investigation. Issue 1 (4th September 2017) - Fischer, Henry H.; Moore, Susan L.; Johnson, Tracy L.; Everhart, Rachel M.; Batal, Holly; Davidsoni, Arthur J.
Introduction: Short Message Service (SMS) appointment reminders may provide a wide-reaching, low cost approach to reducing operational inefficiencies and improving access to care. Previous studies indicate this modality may improve attendance rates, yet there is a need for large-scale, pragmatic studies that include unintended consequences and operational costs. Methods: This pragmatic investigation was a before-after analysis that compared visit attendance outcomes among patients who opted into SMS appointment reminders with outcomes among those who declined over an 18-month evaluation period from March 25, 2013, to September 30, 2014. Eligibility in our integrated safety net health care system included age greater than 17, English or Spanish as a primary language, and a cell phone number in our scheduling system. Results: 47, 390 patients were invited by SMS to participate, of which 20, 724 (43.7 percent) responded with 18, 138 opting in (81.5 percent of respondents). Participants received SMS reminders for 77, 783 scheduled visits; comparison group patients (N=72, 757) were scheduled for 573, 079 visits during the evaluation period. Intervention and comparison groups had, respectively, attendance rates of 72.8 percent versus 66.1 percent (p<0.001), cancellation rates of 13.2 percent versus 18.6 percent (p<0.001), and no show rates of 14.0 percent versus 15.3 percent. Patient satisfaction with text messaging ranged from 77 percent to 96 percent. Implementation challenges included a low rate of inaccurate reminders due to non-standard use of the scheduling system across clinical departments. Discussion: SMS appointment reminders improve patient satisfaction and provide a low operating cost approach to reducing operational inefficiencies through improved attendance rates in an integrated safety net health care system.